Fluorinated porphyrinoids as efficient platforms for new photonic materials, sensors, and therapeutics - Bhupathiraju, N. V. S. Dinesh K. (Org Biomol Chem, 2016)
Porphyrinoids are robust heterocyclic dyes studied extensively for their applications in medicine and as photonic materials because of their tunable photophysical properties, diverse means of modifying the periphery, and the ability to chelate most transition metals. Commercial applications include their use as phthalocyanine dyes in optical discs, porphyrins in photodynamic therapy, and as oxygen sensors. Most applications of these dyes require exocyclic moieties to improve solubility, target diseases, modulate photophysical properties, or direct the self-organization into architectures with desired photonic properties. The synthesis of the porphyrinoid depends on the desired application, but the de novo synthesis often involves several steps, is time consuming, and results in low isolated yields. Thus, the application of core porphyrinoid platforms that can be rapidly and efficiently modified to evaluate new molecular architectures allows researchers to focus on the design concepts rather than the synthesis methods, and opens porphyrinoid chemistry to a broader scientific community. We have focused on several widely available, commercially viable porphyrinoids as platforms: meso-perfluorophenylporphyrin, perfluoro-phthalocyanine, and meso-perfluorophenylcorrole. The perfluorophenylporphyrin is readily converted to the chlorin, bacteriochlorin, and isobacteriochlorin. Derivatives of all six of these core platforms can be efficiently and controllably made via mild nucleophilic aromatic substitution reactions using primary S, N, and O nucleophiles bearing a wide variety of functional groups. The remaining fluoro groups enhance the photo and oxidative stability of the dyes and can serve as spectroscopic signatures to characterize the compounds or in imaging applications using 19F NMR. This review provides an overview of the chemistry of fluorinated porphyrinoids that are being used as a platform to create libraries of photo-active compounds for applications in medicine and materials.